"Ruling out all the wrong, we get to the truth". Case report - E. A. Novokhatskaya; I. V. Kuznetsova; T. A. Ryabinina; G. R. Imametdinova (Кардиоваскулярная терапия и профилактика, 2023)
Polymyalgia rheumatica is a systemic inflammatory disease that is rarely diagnosed in clinical practice due to the low awareness of physicians and the absence of specific diagnostic markers. The case report is of particular interest due to the absence of typical laboratory signs and the presence of concomitant diseases in the patient with similar clinical manifestations. Timely diagnosis and the appointment of adequate therapy made it possible to achieve clinical and laboratory remission without irreversible consequences for the patient’s health.